Report on Native Customs the Bakweri Tribe Victoria Division (Colonial Letters and the Contact of Knowledges, 1921)
This file contains colonil report on native customs of the Bakweris in Victoria Division
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies